Manipulation of calcareous soil pH for temulawak (Curcuma xanthorrizha Roxb.) cultivation - Roviq, Mochammad; Karyawati, Anna Satyana; Sholihah, Puri Kholifatush; Nihayati, Ellis (Brawijaya University, 2023)
Temulawak or Javanese turmeric (Curcuma xanthorrizha Roxb.) has great adaptability and is tolerant of low light intensity; therefore, it may be planted on calcareous soil under teak stands. However, temulawak may thrive in soils with a pH of 5.0-6.5 and plenty of organic matter. Calcareous or alkaline soils have problems with high pH and low organic matter. These conditions can be improved with soil amendments. Manure and other soil amendments can remedy soil structure, chemistry, and organisms. Sulfur is generally used to lower soil pH. Sulfur is a structural component of several coenzymes, chloroplasts, and vitamins essential for plant metabolism. This study aimed to elucidate the effect of manure and sulfur fertilizer on temulawak yield and quality grown on calcareous soil beneath teak stands. This study used a completely randomized block design with two factors: manure doses of 10, 15, and 20 t ha-1 and ZA doses of 0, 40, 80, and 120 kg ha-1. According to the findings, the soil pH to increase the rhizome’s fresh weight per clump is between 5.72 and 6.00. In terms of curcuminoid content and antioxidant activity, the soil pH required by temulawak ranges from 5.94 to 6.61.